Synthesis of double core-shell carbon/silicon/graphite composite anode materials for lithium-ion batteries - Hsu, Yu-Ching; Hsieh, Cheng-Che; Liu, Wei-Ren (Surface & coatings technology, 2020)
In this study, we propose a double core-shell carbon/silicon/graphite composite anode for Li ion batteries. We choose two different sorts of carbon, including crystalline mesocarbon microbeads (MCMB) and amorphous pitch to construct a highly stable carbon matrix to stabilize structural stability of Si during charge and discharge processes. MCMB serves as the core material, by adding nano-sized silicon on the surface to increase reversible capacity and then make a pitch coating as the shell via a high-temperature carbonization process. We try to optimize the content of silicon by 10%, 20%, 30% and 40% onto MCMB. With the increase of silicon content, the reversible capacity is significantly improved. When the silicon content increases to 40%, the reversible capacity begins to decline rapidly. The optimal silicon content in Si/MCMB composite is 30%. The composition-optimized Si/C composite deliver a reversible capacity of 847 mAh/g with a columbic efficiency of 87.8%. After 500 cycles, the capacity still remains at 650 mAh/g with >79% capacity retention. The results indicate that we demonstrate a silicon/carbon composite with high reversible capacity and good cycle stability. [Display omitted] •First attempt to employ a double core-shell Si/C composite as an anode material for lithium ion battery•The double core-shell structure delivered a reversible capacity of 847 mAh/g with 87.8% columbic efficiency in the first cycle.•After 500 cycles, the capacity still remains at 650 mAh/g with >79% capacity retention.